Pendampingan Analisis Potensi Wisata Alam di Desa Medalsari, Kecamatan Pangkalan, Kabupaten Karawang Jawa Barat - Sahara, Lala Siti; Nova, Nova Dian Aprianty; Musyafa, Muhammad Akmal; Arrizkia, Nissa (Satwika: Jurnal Pengabdian Kepada Masyarakat, 2023)
Medalsari Village is located in Base District, Karawang Regency which has the potential tobecome a tourist destination, one of which is natural tourism with a waterfall called GreenCanyon. The main problem faced is the lack of optimal management of natural tourism andthe lack of awareness of local park tourism activists about the innate potential possessed byMedalsari Village. The purpose of this service is to identify and analyse the natural tourismpotential of Medalsari Village and how the direction of its development, using the method ofobserving natural tourism sites, conducting interviews and FGDs with local tourism activists toobtain data used as SWOT analysis material on natural tourism potential so that local tourismactivists, Medalsari Village government understand the concept of natural tourism potentialand its development. The results of the assistance illustrate that Medalsari Village has naturaltourism potential, there are waterfalls and rivers, but it has yet to be maximised in developingthese potentials. Using SWOT analysis, we know the potential, opportunities and challengesthat must be done in developing natural tourism in Medalsari Village.